Measuring the fluid film thickness and evaluation of slope parameter to assess the tribological characteristics of tilting pad bearings. (30th September 2022) - Kim, Kang-Seok; Lee, Deug-Woo; Kim, Mi-Ru; Jung, Yoong-ho
Highlights: Lubrication analysis considered the slope parameter of the friction surface and surface roughness. Relative slope of the pad bearing surface is confirmed to influence the friction characteristics. Fluid film thickness is calculated by analyzing the slope parameter obtained from the friction tests. Experimental values of friction coefficient and slope parameter are compared with numerical analysis. Measured results were to verify lubrication analysis results of tilting pad bearings. Abstract: Researchers studying lubrication analysis have investigated both mixed and hydrodynamic lubrication. Lubrication analysis has been considered with respect to the slope parameter of the friction surface and surface roughness. Furthermore, the relative slope of the pad bearing surface was confirmed to influence friction characteristics. However, whether the lubrication analysis values are comparable to those obtained via friction tests has remained unclear. In this study, we developed an experimental device to obtain the slope parameter and analyzed the results to experimentally verify the lubrication analysis results. The fluid film thickness was calculated by analyzing the slope parameter obtained from the friction tests, and was used as the input value for the lubrication analysis. Thereafter, the experimental values of the friction coefficient and slope parameter were compared with those obtained via numerical analysis.